Reassessing ASEAN Regional Governance in Transnational Narcotics Control through Liberal Institutionalism - Habibi Maulana Al-Fathin; Erdin Prayoga; Elly Nurlia (JISPO : Jurnal Ilmu Sosial dan Ilmu Politik, 2025)
Narcotics circulation and abuse in Southeast Asia have escalated into a transnational threat with significant implications for political stability, public security, and socio-economic development across ASEAN. Rising methamphetamine production in the Golden Triangle and the expansion of cross-border trafficking networks have reinforced the urgency of ASEAN’s collective response through the Drug-Free ASEAN 2025 agenda. This study aimed to assess the effectiveness of cooperation among Indonesia, Malaysia, Thailand, and Vietnam in implementing this agenda, using Robert O. Keohane’s Liberal Institutionalism to explain how cooperation can persist in the absence of hegemonic enforcement. The study employed a qualitative descriptive approach based on a structured literature review of 25 scholarly journal articles, ASEAN policy reports, and secondary documents from UNODC and Indonesia’s National Narcotics Agency (BNN). The findings showed that ASEAN cooperation generated meaningful institutional and diplomatic progress, particularly through mechanisms such as ASOD, AMMTC, and ASEANAPOL that facilitated coordination, information exchange, and operational networking. However, substantive effectiveness in suppressing trafficking remained constrained by legal-system divergence, uneven national capacity, inconsistent transparency, and weak joint evaluation and monitoring arrangements. The study concluded that ASEAN’s anti-narcotics cooperation operated as a form of non-hegemonic institutional governance sustained by trust, reciprocity, and normative compliance, yet required stronger implementation linkages to achieve measurable impact. The study contributed theoretically by extending Liberal Institutionalism to ASEAN’s non-traditional security governance and practically by recommending strengthened data integration, peer performance review, legal harmonization, and technology-oriented responses to emerging digital trafficking.